2021
DOI: 10.2147/copd.s297087
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Clinical Phenotypes, GOLD Groups/Stages and Mortality in COPD Patients – A Prospective Multicenter Study

Abstract: Introduction The concept of phenotyping emerged, reflecting specific clinical, pulmonary and extrapulmonary features of each particular chronic obstructive pulmonary disease (COPD) case. Our aim was to analyze prognostic utility of: “Czech“ COPD phenotypes and their most frequent combinations, ”Spanish” phenotypes and Global Initiative for Chronic Obstructive Lung Disease (GOLD) stages + groups in relation to long-term mortality risk. Methods Data were extracted from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
0
3
1
4
Order By: Relevance
“…De esta clasificación, se ha demostrado que el grado 4 y grupo E se asocian a mayor riesgo de mortalidad y peor pronóstico, lo que nuevamente confirma el impacto negativo de las exacerbaciones en los desenlaces del paciente . 3,15,38 Figura 1.…”
Section: Fenotiposunclassified
See 3 more Smart Citations
“…De esta clasificación, se ha demostrado que el grado 4 y grupo E se asocian a mayor riesgo de mortalidad y peor pronóstico, lo que nuevamente confirma el impacto negativo de las exacerbaciones en los desenlaces del paciente . 3,15,38 Figura 1.…”
Section: Fenotiposunclassified
“…De manera particular, la literatura ha evidenciado que la mayor carga de la enfermedad y el mayor uso de recursos se destina a tratar las exacerbaciones debido al requerimiento de manejo más agresivo, incluyendo el uso de la sala de urgencias, hospitalización, Unidad de Terapia Intensiva (UTI) y el incremento de tratamiento farmacológico; como lo enfatizan los resultados del estudio ARTIC 26 y recientemente en el Panel Delphi de expertos mexicanos Evaluación del costo en pacientes con Enfermedad Pulmonar Obstructiva Crónica (EPOC) dentro de la perspectiva pública de salud. 38 En otro estudio 10 se encontraron costos médicos totales, en el uso de servicios de urgencias, hospitalización y de farmacia progresivamente mayores conforme progresaba la etapa GOLD y sus tasas de exacerbaciones.…”
Section: Costosunclassified
See 2 more Smart Citations
“…For example, longitudinal studies conducted in Spain and the Czech Republic have consistently shown a higher mortality risk in patients with an exacerbation phenotype (with or without chronic bronchitis), compared with NON-AE and those with ACOS. [5][6][7] Other studies have shown that a clustering approach, which groups patients based on clinical features such as comorbidities, dyspnea, and lung function, is also a useful predictor of mortality. [8][9][10][11][12] In one study, cluster analysis was found to be significantly superior to the 2017 Global Initiative for Chronic Obstructive Lung Disease (GOLD) 1-4 spirometry classification system for predicting mortality, with similar predictive ability to other systems such as the body mass index (BMI), obstruction, dyspnea and exercise (BODE) index and the GOLD ABCD classification.…”
Section: Introductionmentioning
confidence: 99%